2016
DOI: 10.4103/0970-9290.195641
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of frictional resistance and surface characteristics after immersion of orthodontic brackets and wire in different chemical solutions: A comparative in vitrostudy

Abstract: Findings may have long-term implications when acidic food substances are used during fixed orthodontic treatment. Further, in vivo studies are required to analyze the clinical effect of acidic mediums in the oral environment during orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…He stated that the change in the LFM-acquired frictional resistance was similar to that of the AFM-acquired surface roughness. Nanjundan and Vimala18 concluded that a significant positive correlation was observed between the frictional force, bracket slot roughness, and wire roughness. The results of the present experiment are consistent with those of Choi et al15 and Nanjundan and Vimala 18…”
Section: Discussionmentioning
confidence: 98%
“…He stated that the change in the LFM-acquired frictional resistance was similar to that of the AFM-acquired surface roughness. Nanjundan and Vimala18 concluded that a significant positive correlation was observed between the frictional force, bracket slot roughness, and wire roughness. The results of the present experiment are consistent with those of Choi et al15 and Nanjundan and Vimala 18…”
Section: Discussionmentioning
confidence: 98%
“…Surface roughness can affect the amount of friction that occurs during orthodontic treatment, although the influence of the surface roughness of the wire arc also plays a role. 9 Choosing a bracket with a good surface roughness is very important, but the process of making a bracket by the factory is not always perfect because there are still grooves and marks on the surface of the bracket slot. 1 Standardisation by the International Organization for Standardization (ISO) is crucial as a guide for manufacturing brackets by manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated higher static and kinetic frictional forces in the Pepsi group and the greatest surface roughness. 27 However, the limitation of the latter study is that it was conducted after continuous 24-hour exposure to the acidic solution, whereas intraoral pH levels rather oscillate than remain constant.…”
Section: Discussionmentioning
confidence: 99%